Extending the Simultaneous-Sequential Paradigm to Measure Perceptual Capacity for Features and Words. - Scharff, Alec; Palmer, John; Moore, Cathleen M. (Journal of Experimental Psychology. Human Perception & Performance, 2011)
In perception, divided attention refers to conditions in which multiple stimuli are relevant to an observer. To measure the effect of divided attention in terms of perceptual capacity, we introduce an extension of the simultaneous-sequential paradigm. The extension makes predictions for fixed-capacity models as well as for unlimited-capacity models. We apply this paradigm to two example tasks, contrast discrimination and word categorization, and find dramatically different effects of divided attention. Contrast discrimination has unlimited capacity, consistent with independent, parallel processing. Word categorization has a nearly fixed capacity, consistent with either serial processing or fixed-capacity, parallel processing. We argue that these measures of perceptual capacity rely on relatively few assumptions compared to most alternative measures. Reprinted by permission of the publisher.